Developing Proprioceptive Countermeasures to Mitigate Postural and Locomotor Control Deficits After Long-Duration Spaceflight - Macaulay, Timothy R.; Peters, Brian T.; Wood, Scott J.; Clément, Gilles R.; Oddsson, Lars; Bloomberg, Jacob J. (Frontiers in Systems Neuroscience, 2021)
Astronauts experience postflight disturbances in postural and locomotor control due to sensorimotor adaptations during spaceflight. These alterations may have adverse consequences if a rapid egress is required after landing. Although current exercise protocols can effectively mitigate cardiovascular and muscular deconditioning, the benefits to postflight sensorimotor dysfunction are limited. Furthermore, some exercise capabilities like treadmill running are currently not feasible on exploration spaceflight vehicles. Thus, new in-flight operational countermeasures are needed to mitigate postural and locomotor control deficits after exploration missions. Data from spaceflight and from analog studies collectively suggest that body unloading decreases the utilization of proprioceptive input, and this adaptation strongly contributes to balance dysfunction after spaceflight. For example, on return to Earth, an astronaut’s vestibular input may be compromised by adaptation to microgravity, but their proprioceptive input is compromised by body unloading. Since proprioceptive and tactile input are important for maintaining postural control, keeping these systems tuned to respond to upright balance challenges during flight may improve functional task performance after flight through dynamic reweighting of sensory input. Novel approaches are needed to compensate for the challenges of balance training in microgravity and must be tested in a body unloading environment such as head down bed rest. Here, we review insights from the literature and provide observations from our laboratory that could inform the development of an in-flight proprioceptive countermeasure.